HEALTH RISK ASSESSMENT OF HEAVY METALS IN MICROPLASTICS FROM SURFACE WATERS IN OTUOKE, NIGER DELTA - Okonkwo , Chinedu Sylvester (Ayden Journal of Engineering and Applied Sciences, 2025)
Microplastics serve as vectors for heavy metals in aquatic environments, posing potential ecological and human health risks. This study assessed the concentrations of cadmium (Cd), copper (Cu), chromium (Cr), iron (Fe), manganese (Mn), nickel (Ni), lead (Pb), and mercury (Hg) adsorbed onto microplastics in surface water (MCPWs) from the Otuoke River, South-South Nigeria, during dry and wet seasons. Samples were digested using the US EPA 3050B method and analyzed via Flame Atomic Absorption Spectrophotometry (FAAS). The ecological and human health risks were evaluated through hazard quotient (HQ) and hazard index (HI) assessments. Results showed seasonal variations in metal concentrations, with significantly higher values recorded during the dry season (p < 0.05). The highest Cu (41.06 ± 6.67 mg/kg) and Mn (133.22 ± 2.71 mg/kg) levels were detected at STA- , while Fe concentrations peaked at STA-3 (13,932.68 ± 489.70 mg/kg). HI values for children were notably higher than those for adults, indicating greater susceptibility. Dry season HI values suggested potential health risks for adults (HI > 1) and significant health risks for children (HI > 10). Wet season assessments showed reduced metal bioavailability, with no significant risks for adults at certain locations (HI < 1), though children remained at potential risk. The study underscores the urgent need for mitigation strategies to curb heavy metal contamination in MPs and reduce public health threats. These findings contribute to understanding MPs as contaminant carriers and highlight the necessity for stricter environmental regulations and public awareness campaigns